Pengaruh Profitabilitas, Leverage, Dan Komposisi Dewan Komisaris Independen Terhadap Pengungkapan Corporate Social Responsibility - Fitri Herdi; Erinos NR (Universitas Negeri Padang, 2020)
This study aims to determine the effect of profitability, leverage, and the composition of the independent board of commissioners on the disclosure of corporate social responsibility. The population in this study were mining companies listed on the Indonesia stock Exchange (IDX) in 2014 to 2018. The research sample was determined using a purposive sampling method, and a total sample of 10 mining companies. The data used is secondary data. Data collection techniques with documentation at www.idx.co.id . The analytical method used is Moderated Regression Analysis. The results showed that profitability had a positive and not significant effect on CSR, leverage had a negative and not significant effect on CSR, and the composition of the independen board of commissioners had a negative and not significant effect on CSR